The Values School of Davao strategic plan - Salili, Cheryl T.; Concepcion, Sylvia B.; Soledad, Miguel D. (Davao City School of Management, University of the Philippines Mindanao, 2010)
Values School of Davao was first established in 1994. Its owner, Ma?am Aida Lacsamana Reyes drew her inspiration from her mother, the late Vicenta Alcantara Lacsamana, who established the Light Bringer School in the sixties. It is the school?s vision that character development and values formation is as much important as academic excellence. It carries with it two generations of teachers who are dedicated and committed. Presently, the school has already two campuses, its main campus in Matina, and another campus in Marfori. The school offers classes for preschool and elementary. With their new building in Matina campus, Values School tries to live up to its name and continues to evolve and grow to meet the constantly changing needs of the students and the school. With its current Vision, Mission, Philosophy, present challenges and opportunities, this paper had set the school?s direction for the next five years. Using Fred David?s Strategic Management Framework, this paper examined the internal and external factors for Values School of Davao to assess its present condition. After gathering all necessary information, setting of goals for the organization based on its vision was made. These goals will determine where the organization would want to go, provide the basic direction for the activities of the school for the next five years in pursuit of its mission. Tools like SWOT Matrix, IE Matrices, and the QSPM were used to formulate strategies. Applying the QSPM, different strategic alternatives (Product Development, Market Penetration, and Operational Efficiency) were ranked to choose which one will help the organization attain its goals and objectives. In the implementation stage, proper implementation of the identified programs that will address the goals and objectives of the organization will be done accordingly. With continuous effort for market penetration, product development, and operational efficiency, this paper will closely monitor progress through development of control system and key result areas.
Thesis, Graduate (Master in Management)--University of the Philippines, Mindanao, March 2010.